A Different Way of Working: Embedding Clinical Psychology Placements in Third Sector Organisations Supporting People Experiencing Homelessness - Hannah Frith; Mary John; Leah Sharkah; Jane Iles (Health Expectations, 2025)
ABSTRACT Objectives People experiencing homelessness experience high levels of trauma and psychological distress, but rarely access or engage with formal mental health services. The National Framework for Inclusion Health highlights collaboration between the NHS and third sector organisations as essential for reducing health inequalities. Providing clinical placements in third sector organisations for clinical psychology trainees may offer a valuable route to addressing this gap, whilst providing a beneficial learning experience. Methods Qualitative semi‐structured interviews with clinical psychology trainees, staff in homeless settings and a clinical supervisor were used to explore perceptions of clinical placements and the benefits and challenges experienced by those involved in delivering these placements. Reflective thematic analysis was used to identify key themes in the perceptions of staff, supervisors and trainees. Results Three key themes were developed. (1) Bringing a psychological mindset reflected the value that homelessness organisations placed on being helped to think about their client work through a psychological lens and extending this lens to also consider staff well‐being. (2) Breaking barriers and building bridges describes how trainees were positioned as brokers who could connect homelessness organisations to formal mental health systems and could advocate for homeless people within these systems in ways which may have long‐term effects. (3) Working and learning differently captures how these placements required trainees to work differently by crafting new roles and by adopting different working practices, including navigating complex issues around risk. Conclusions Clinical psychology placements within homelessness organisations may help meet the objectives of the NHS National Framework for Inclusion Health by helping create PIEs in homelessness organisations, navigating connections between statutory and third sector organisations, and creating a skilful workforce adept at managing cultural mistrust.